Development of a quick response encyclopedia (QR code) of fish catches of fishermen in air nusa serasan village natuna regency - Erlianti, Erlianti; Setiadi, Anandita Eka; Sunandar, Ari Sunandar (JURNAL BIOEDUKATIKA, 2024)
The learning resources used at SMAN 1 Serasan have not used the local potential found in the Natuna Regency. Therefore, a learning resource is needed to provide a real picture of the biodiversity material students know. Based on a QR Code, this study aimed to measure the feasibility and analyze student responses to the Encyclopedia of Fish Catches of Air Nusa Serasan Village Fishermen of Natuna Regency. This research uses the research and development method with the 4D development model, namely define, design, develop, and disseminate. The dissemination stage was not carried out due to limited time and cost. The results showed that the feasibility of the encyclopedia was very feasible in the language aspect (85.6%), material aspect (89.13%), and media aspect (89.31%). Student responses showed a positive response with a small-scale value of 79,68% and a large-scale value of 87.92%. It is concluded that the QR Code-Based Fishermen’s Catch Encyclopedia Media in Air Nusa Serasan Village, Natuna Regency, is suitable for student biology learning.